Cross-dehydrogenative coupling: a sustainable reaction for C-C bond formations - Tian, Tian; Li, Zhiping; Li, Chao-Jun (Green chemistry : an international journal and green chemistry resource : GC, 2021)
We are entering an era that emphasizes greenness and sustainability. Based on such a philosophy, it is critical to uncover novel and original sustainable reaction modes for future green chemical syntheses. The cross-dehydrogenative coupling (CDC) reaction has thus been widely developed as one of the most sustainable and efficient synthesis strategies for constructing C-C bonds. This review summarizes the development of this field over the past 20 years, with a discussion on future trends and directions: from the original reaction model at the beginning and its development in the first decade, to extensive research in the second decade. The latest development sees the emergence of alternative forms of energy inputs (photoredox, mechano, microwave, electrochemical, continuous-flow and solar quantum dots) to facilitate CDC reactions, gradually replacing the classical form of thermal energy, which will inspire broader applications and innovations in the future. We provide a review of the progress of cross-dehydrogenative coupling reactions in constructing a wide variety of C-C bonds. Sustainable cross-dehydrogenative coupling reactions can be combined with multiple forms of energy output.